ANALISIS PENGGUNAAN KONTRASEPSI SUNTIK TERHADAP PENINGKATAN TEKANAN DARAH - Setyorini, Catur; Hanifah, Lilik; Lieskusumastuti, Anita Dewi; Febriani, Anggi (Jurnal Komunikasi Kesehatan, 2022)
Family planning acceptors who use hormonal contraception (pills and injections) for a certain period of time often complain of health problems, one of which is hypertension or high blood pressure. Determining the relationship between the use of injectable contraception and the increase in blood pressure. This is an analytical study with a Cross-Sectional approach. The sample in this study is 34 acceptors of injection for family planning at Independent Midwife Practice Asih Ngemplak Boyolali in January - March 2022. The data is collected by using secondary data. The data is analyzed by using the Chi-Square test. Respondents who use injectable contraceptives per month are 18 respondents (53%) and those who use injectable contraceptives per 3 months are 16 respondents (47%). Among 18 respondents who use 1- month injectable contraception, 1 respondent (5%) experience an increase in blood pressure and 17 respondents (95%) do not experience an increase in blood pressure. Meanwhile, among 16 respondents of 3-month injectable contraception, 2 respondents (13%) experience an increase in blood pressure and 14 respondents (87%) do not experience an increase in blood pressure. The statistical test showed that the use of injectable contraceptives does not relate to the increase in blood pressure with a p-value of 0.48 (p>0.05). The use of injectable contraceptives does not relate to the increase in blood pressure.